KORUPSI DAN MASA DEPAN BANGSA (Suatu Pendekatan Daruriyah al-khamsah) - Rasyid, Muh. Haras (DIKTUM: Jurnal Syariah dan Hukum, 2010)
Corruption is a crime that is harmful to the life of the nation, to day and the future. Corruption in Indonesia has become culture and difficult cure disease, because it was rampant in bureaucratic institutions. The question that arises is the law enforcement and all existing legal rules as the expectations of society are not able to eradicate corruption. This paper analyzes about how the advantages and disadvantages caused by corruption in national life through approach âDaruriyah al-Khamsahâ, namely the advantages theory in Islam. The purpose of this paper is to understand the corruption and its danger, so it can be avoided for individual advantages and the future of the Indonesia nation. The method used is the analysis methods with an approach calibrated between the approach of theology, law, economics and sociology.